(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Asthma is a common inflammatory airway illness that is treated mostly with inhaled corticosteroids (ICS). Managing severe asthma, which affects 5% to 10% of asthma patients, remains challenging even with high doses of inhaled corticosteroids and anti-inflammatory medications. ICS can have side consequences such as hypothalamic-pituitary-adrenal axis suppression, reduced growth velocity, osteoporosis, diabetes, and respiratory infections, which can negatively impair the quality of life for severe asthmatics. We here summarize the evidence of inhaled corticosteroids related adverse effects, particularly in patients with asthma. Early use of biologic medicines for severe asthma can minimize unwanted effects and lower costs associated with corticosteroid use.